"Ecology of fear" in ungulates: Opportunities for improving conservation. Issue 3 (1st March 2022) - Chitwood, M. Colter; Baruzzi, Carolina; Lashley, Marcus A.
Abstract: Because ungulates are important contributors to ecosystem function, understanding the "ecology of fear" could be important to the conservation of ecosystems. Although studying ungulate ecology of fear is common, knowledge from ungulate systems is highly contested among ecologists. Here, we review the available literature on the ecology of fear in ungulates to generalize our current knowledge and how we can leverage it for conservation. Four general focus areas emerged from the 275 papers included in our literature search (and some papers were included in multiple categories): behavioral responses to predation risk (79%), physiological responses to predation risk (15%), trophic cascades resulting from ungulate responses to predation risk (20%), and manipulation of predation risk (1%). Of papers focused on behavior, 75% were about movement and habitat selection. Studies were biased toward North America (53%), tended to be focused on elk ( Cervus canadensis ; 29%), and were dominated by gray wolves (40%) or humans (39%) as predators of interest. Emerging literature suggests that we can utilize predation risk for conservation with top‐down (i.e., increasing predation risk) and bottom‐up (i.e., manipulating landscape characteristics to increase risk or risk perception) approaches. It is less clear whether fear‐related changes in physiology have population‐level fitness consequences or cascading effects, which could be fruitful avenues for future research. Conflicting evidence of trait‐mediated trophic cascades might be improved with better replication across systems and accounting for confounding effects of ungulate density. Improving our understanding of mechanisms modulating the nature of trophic cascades likely is most important to ensure desirable conservation outcomes. We recommend future work embrace the complexity of natural systems by attempting to link together the focal areas of study identified herein. Abstract : In this review, we highlight the need to diversify research efforts on the ecology of fear in ungulates. We show that most of the literature found with our search disproportionately focused on a few prey and predator species, especially in North America, while several species and systems were highly underrepresented.